Creativity with care during COVID-19 - Paul Sullivan (Scottish Journal of Residential Child Care)
The importance of music and creativity in promoting the social development and wellbeing of children and young people is well documented. For children and young people with care experience, music can build resilience, help to heal trauma and support the development of supportive relationships; however, despite these myriad benefits, significant challenges remain that prevent care experienced children and young people's access to creativity. This article explores the impact of these challenges, many of which are being exacerbated by COVID-19; and, shines a light on one initiative 'Musicares' that is helping to overcome these challenges in Scotland.